AGROWISATA BUAH-BUAHAN DI BATI-BATI DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Simanto, Fransiskus Kelvin; Aufa, Naimatul (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Tourism trends in Indonesia are currently experiencing a transformation from mass tourism to alternative tourism that prioritizes natural and cultural potential. Tanah Laut Regency, which is projected to become an agricultural center, has the potential to develop natural and cultural tourism. One of them is in Bati-Bati District as a center for local activities based on processing industry and agriculture. PT. Air Telaga Surya as one of the mineral water companies in Bati-Bati District has plans to develop its area into a fruit agro-tourism area. However, the development of the area is hampered by the existence of land used for traditional diamond mining which has become an abandoned, polluted lake and has harmed the environment. Therefore, the development of a fruit agrotourism area aims to produce an area design that combines elements of plantations, local social culture, and ecological restoration of the area so as to create sustainable tourism. For this reason, the concept of Hayat Basulur was initiated, which is an ecological concept that is analogous to the nature of rhizomes which means they grow together. The tendrils on the rhizomes that bind each other are analogous to the character of agrotourism that harmonizes human activities, local culture and the post-mining environment. The three of them grow together to build a sustainable and ecological tourism ecosystem through the regional planning, the architecture and the connectivity.